Le fratture trasverse di acetabolo e il loro trattamento - Bersano, A.; Aprato, A.; Zoccola, K.; Favuto, M.; Cominetti, G.; Conforti, L.; Massè, A. (Lo Scalpello - Journal, 2018)
TRANSVERSE ACETABULAR FRACTURES Transverse acetabular fractures are demanding and challenging for orthopaedic surgeons and they represent up to 22% of all acetabular fractures. They involve either the anterior or the posterior column; reduction of both columns may not be easy using a single approach. Usually the iliofemoral or the Langenbeck approaches are used to reduce and fix those fractures but their limit is poor control in the reduction of the opposite column. A safe hip dislocation technique has been proposed to avoid this limit and in the literature good results are reported. Anatomic reduction and stable fixation are essential to achieve good results and to procrastinate arthritis in young patients. In the elderly, transverse fractures may be treated with direct total hip arthroplasty associated with posterior column fixation although these treatments involve high complications rates.